The Role of Moral Creed Teachers in Instilling Social Attitudes in Students at Madrasah Aliyah Darul Ulum - Hasanah, Putri Nikmatul; Ehwannudin, Ehwannudin; Wijaya, Adi (International Journal on Advanced Science, Education, and Religion, 2025)
The problems faced by teachers of moral beliefs in instilling attitudes social values ​​among students at Madrasah Aliyah Darul Ulum, namely the lack of practical activities to practice social values ​​at Madarsah Aliyah Darul Ulum and the process of learning moral beliefs is more focused on theory without being equipped with practical activities that involve real social interactions such as social service activities, mutual cooperation, so that students do not get the opportunity to practice social values ​​directly. This research was carried out at Madarsah Aliyah Darul Ulum which is located in the Bone Bawang Barat district of the village. Panaragan Jaya, in the 2025 academic year. This research aims to determine the role of moral aqidah teachers in instilling social attitudes in students at Madrasah Aliyah Darul Ulum. This research uses a qualitative approach with descriptive methods. In this research, the researcher used several data collection tools, namely through interviews, observation and documentation involving the madrasa head, moral aqidah teachers and students as research subjects. This research uses source triangulation. This research finds that moral belief teachers have a strategic role in instilling social attitudes in students through example, interactive learning, integration of moral values, and habituation in the school environment. With an effective approach, students can develop positive social attitudes and apply them in everyday life. The research results show that there are efforts made by moral aqidah teachers in instilling social attitudes in students at Madrasah Aliyah Darul Ulum, students become more polite, helpful, have a sense of empathy, strengthen cooperation and tolerance, behave fairly and honestly